THINKING WITH ROY AND ŽIŽEK ON THE FREEDOM OF A FORCED COVID-19 ‘NEW NORMAL’ - Allan Abiera; Prakriti Mukherjee; Jan Gresil Kahambing (International Journal of Humanity Studies (IJHS), 2022)
The increasing imagination of crisis within the contemporary scene is set within the state of emergency that is the Coronavirus disease 2019 (COVID-19) pandemic. In this background, there is the problem of redefining the conditions of normality. The paper aims to take some insights about how to think through this predicament from Arundhati Roy and Slavoj Žižek who are, the authors deemed, subversives against the normal regulatory course of thought. To do this, the study applies the method of textual hermeneutics on both thinker’s oeuvre, particularly those that relate to the pandemic and specifically Roy’s AZADI and Žižek’s Pa(ndem)ic! 1 and 2, and contextualizes their energetic radical visions to one of the co-authors’ compiled takes on various cases during COVID-19. In this paper’s reading, which attempts to succinctly open a leeway for such takes by aligning the implications with both thinkers’ views for thinking forward and enacting possibilities, Roy’s resolve through love and Žižek’s notion of a forced choice can be reflected on in traversing the inevitable portal of the ‘New Normal.’